The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/dom.12447
|View full text |Cite
|
Sign up to set email alerts
|

A novel peripheral cannabinoid receptor 1 antagonist, BPR0912, reduces weight independently of food intake and modulates thermogenesis

Abstract: BPR0912 exhibits significant in vivo efficacy in inducing food intake-independent weight loss in DIO mice, while tending to reduce their hepatic steatosis. The thermogenic effects of BPR0912, as well as its modulation of protein and gene expression patterns in WAT and BAT, may enhance its efficacy as an anti-obesity agent. The results of the present study support the benefits of the use of peripheral CB1R antagonists to combat metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…CB1R blockade also increases BAT UCP-1 expression [22,72]. Consistently, rimonabant treatment increases energy expenditure and BAT temperature [72,73], and Hsiao et al [74] demonstrated that chronic peripheral inhibition of CB1R by BPR0912 induced UCP-1 expression in BAT of mice and elevated core body temperature, indicating increased thermogenic activity of BAT. Importantly, BAT can be visualized in rats using radioactive PET ligands with high affinity for CB1R, thereby demonstrating its dense presence in the tissue in vivo [75].…”
Section: Cb2r Signaling In Watmentioning
confidence: 71%
“…CB1R blockade also increases BAT UCP-1 expression [22,72]. Consistently, rimonabant treatment increases energy expenditure and BAT temperature [72,73], and Hsiao et al [74] demonstrated that chronic peripheral inhibition of CB1R by BPR0912 induced UCP-1 expression in BAT of mice and elevated core body temperature, indicating increased thermogenic activity of BAT. Importantly, BAT can be visualized in rats using radioactive PET ligands with high affinity for CB1R, thereby demonstrating its dense presence in the tissue in vivo [75].…”
Section: Cb2r Signaling In Watmentioning
confidence: 71%
“…CB1R antagonist rimonabant (SR141716) was previously in clinical use with strong efficacy for weight loss, but was withdrawn because of serious psychiatric adverse effects (14). Recently, novel CB1R antagonists, which act strictly peripherally, have been found to activate BAT in rodents, inducing lipolysis and lipid oxidation, thus improving metabolism (15,16). Activation of BAT via CB1R antagonism without harmful centrally mediated adverse effects could be one way to improve metabolic disease and combat obesity in humans (17).…”
mentioning
confidence: 99%
“…Verty triglycerides, and hepatic triglycerides were observed with both compounds, but compared to rimonabant, BPR0912 raised fatty acid oxidation-related gene expression and thermogenesis more significantly (Hsiao et al 2015). In summary, activation of CB1 receptors contributes to increased appetite, suppressed energy expenditure, and when deranged, obesity.…”
Section: Appetite and Energy Expenditurementioning
confidence: 88%